(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study aimed to prepare posaconazole (PNZ) microsponges and formulate them into a hydrogel, optimizing the drug-polymer ratio and other parameters using Design Expert’s box behnken design. The microsponges were synthesized considering drug-polymer ratio, surfactant (PVA), and stirring speed as inputs, while the vesicular size and PNZ content were evaluated as dependent variables. The prepared microsponges were then merged into a hydrogel. Compatibility studies between the PNZ and excipients were conducted, and the physicochemical parameters of the microsponges and hydrogels were assessed. Statistical analysis was performed to evaluate variance among the factors. Microsponges formulated with a polymer ratio of 1:1 with PNZ (PM-3) exhibited favorable attributes, including smaller vesicular size, drug content, high %yield, %entrapment, and superior PNZ discharge profile. Scanning electron microscopy confirmed the round morphology and spongy assembly of PM-3 microsponges, indicating their suitability for PNZ loading and release. In-vitro release studies demonstrated rapid initial discharge followed by sustained release over 12 hours for PM-3, indicating potential for optimized PNZ delivery. Viscosity studies revealed a higher viscosity of PM-3 gel compared to conventional gel, potentially enhancing adherence to the skin surface and PNZ absorption. Additionally, PM-3 exhibited superior antifungal activity in disk diffusion assays, indicating effective control of fungal growth. This study successfully developed PNZ-loaded microsponge hydrogels, showing promising utility in treating fungal infections. PM-3 formulation demonstrated superior characteristics, suggesting its potential for optimized PNZ delivery and therapeutic outcomes.